Pengaruh Profitabilitas, Kebijakan Dividen, Growth Opportunity, Dan Struktur Modal Terhadap Nilai Perusahaan - Aditya Muhamamd Rafly Rizantha (CV. KAMPUS AKADEMIK PUBLISING, 2024)
The Effect of Profitability, Dividend Policy, Growth Opportunity, and Capital Structure on Firm Value (Study on the Consumer Non-Cyclicals Sector on the IDX for the 2019 - 2022 Period)This study aims to examine the effect of profitability, dividend policy, growth opportunity and capital structure on firm value. The population in this study were all Consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2019-2022. The variables used in this study are Firm Value as the dependent variable; Profitability, Dividend Policy, Growth opportunity and Capital Structure as independent variables. The sampling technique used was purposive sampling method and obtained 92 companies. The analysis method used is Descriptive Statistical Analysis, Classical Assumption Test, Correlation Test, Multiple Linear Regression Test, and Hypothesis Test. The results showed that Profitability has a positive effect on Company Value, Dividend Policy has no effect on Company Value, Growth opportunity has no effect on Company Value, and Capital Structure has a positive effect on Company Value.